Linear Optimization Modelling for Profit Maximization in Bakery Store - Abdul Aziz, Nur Syafinaz; Kek, Sie Long (Enhanced Knowledge in Sciences and Technology, 2024)
The bakery industry is a dynamic and rapidly evolving sector with a significant economic impact globally. However, running a bakery business poses challenges due to perishable products and the need for efficient resource management. This study explores the application of linear programming in bakery management to maximize profits while considering resource availability and product selection constraints. The effectiveness of Microsoft Excel’s ’Solver’ tool is demonstrated, and the research concludes that linear programming can significantly improve efficiency and profitability in bakery operations. The results show a maximum daily profit of RM142.92 by producing three batches of Cheese Bread and 1 batch of each Sugar Bread, Blueberry Bread, and Red Bean Bread. Overall, this study highlights the potential of linear programming as a valuable tool in optimizing bakery operations and increasing profitability.